Examining The Effects of Motivation and Anxiety on EFL Students’ Speaking Assessments - Fairuz Lazuwardiyyah (Indonesian Journal of Foreign Language Studies, 2025)
In the field of English language instruction, speaking assessment is of utmost importance because it is one of the abilities that students are expected to acquire. Some students, on the other hand, have feelings of both motivation and anxiety during their speaking examination. As a result, the purpose of this study is to investigate the influence that motivation and anxiety have on the speaking assessments of English as a Foreign Language students. From 57 (fifty-seven) English as a Foreign Language (EFL) students in their second semester, data was collected through the use of quantitative methodologies by means of questionnaires that measured levels of motivation and anxiety. Despite the fact that students are generally very driven to study and speak English, the findings suggest that they experience varied degrees of anxiety, particularly when it comes to speaking exams. Based on the findings of regression analysis, motivation has a favorable influence on speech assessment scores, whereas anxiety has a negative influence on these scores. The outcomes of this study highlight the significance of effectively controlling anxiety and improving motivation in order to improve the academic performance and speaking ability of English as a Foreign Language (EFL) students. Therefore, future research still needs to explore how various motivational types, such as intrinsic or extrinsic, affect EFL students' speaking ability and how these types interact with anxiety.